THERMAL EFFICIENCY ANALYSIS OF COMBUSTION TURBINE GENERATOR (821-G-101) PT TRANS PACIFIC PETROCHEMICAL INDOTAMA AFTER MAJOR INSPECTION - Arif Batutah, Moh; Kusnanto, Hadi; Kurniawati, Indah; Safi’i , Achmad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The gas turbine is one of the most widely used equipment in oil and gas industries as an electric generator driving system. To maintain the reliability and performance of the gas turbine, a major inspection program is required. Thermal efficiency analysis is the parameters of success in major inspection activities. Thermal efficiency analysis is carried out by comparing data and operating parameters of gas turbine before and after the major inspection. The analysis aims to determine the actual efficiency of each component, and also the actual overall efficiency in the gas turbine. The study result is the actual thermal efficiency of a gas turbine after a major inspection has increased from 12.20% to 12.84% at a load of 6 MW, an increase from 15.76% to 16.77% at a load of 9 MW, and an increase of 18.59% to 20.16% at a load of 12 MW. Based on the actual performance comparison data with design data, it is known that the overall actual performance is still below the design performance, both heat efficiency, heat consumption and heat rate. This is caused by the operating lifetime